2022
DOI: 10.3390/w14071152
|View full text |Cite
|
Sign up to set email alerts
|

Wetlands in China: Evolution, Carbon Sequestrations and Services, Threats, and Preservation/Restoration

Abstract: China has a wetland area of 53.42 million hectares, the fourth largest in the world; it includes all types of wetlands defined by the Ramsar Convention and has a carbon sink capacity of more than 1.71 million metric tons per year. Inland wetlands in China are mainly distributed in 10 major catchments, among which the Yellow River, the Yangtze River, the rivers in the northwest, and the rivers in the northeast each have more than 8 million hectares of wetlands. There are 4220 species of plants and 4015 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Within the last decade, a series of wetland protection and restoration policies have been imposed on floodplain lakes along the Yangtze River. (Zhao et al, 2019;Xie et al, 2022;Ye et al, 2022). And these policies were carried out in Caizi Lake, including a ban on pen-culture and fishing (Wang, 2020).…”
Section: Implications For Wintering Bird Habitat Management and Prote...mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last decade, a series of wetland protection and restoration policies have been imposed on floodplain lakes along the Yangtze River. (Zhao et al, 2019;Xie et al, 2022;Ye et al, 2022). And these policies were carried out in Caizi Lake, including a ban on pen-culture and fishing (Wang, 2020).…”
Section: Implications For Wintering Bird Habitat Management and Prote...mentioning
confidence: 99%
“…Over the past half-century, wide scale and high density of aquaculture and agriculture resulted in lake degeneration, and creating paddy fields and aquaculture ponds. However, within the last decade, a series of wetland protection and restoration policies have been imposed on floodplain lakes along the Yangtze River, for example, recovering lakes by stopping land reclamation, and a ban on pen-culture and fishing (Zhao et al, 2019;Xie et al, 2022;Ye et al, 2022). Furthermore, appropriate action is needed to explore the utilization of the historic paddy fields and aquaculture ponds for waterbird conservation and wetland management.…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands are well known as the kidney of the earth with abundant biological resources and ecological functions such as purifying the water source, mitigating floods and droughts, and regulating regional microclimate (Chakraborty et al., 2023; Ye et al., 2022). In recent years, increasing numbers of reports have confirmed that AM fungi also exist widely in wetland habitats and can colonize the roots of various hygrophytes to form AM symbiotic structure (Xu et al., 2016; Yan et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of carbon sequestration by herbaceous marsh vegetation is faster than that of other types of marsh vegetation ( Zhou et al., 2009 ). Herbaceous marshes play a critical role in regulating regional carbon cycle ( Ye et al., 2022 ). The NPP of herbaceous marsh is a significant indicator of herbaceous marsh ecosystem functions and capacity for carbon sequestration ( Woltz et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%